Multiplicative Schwarz algorithms for the p-version Galerkin boundary element method in 3D - Maischak, Matthias (Applied numerical mathematics, 2006)
We study a 2-level multiplicative Schwarz method for the p version Galerkin boundary element method for a weakly singular integral equation of the first kind in 3D. We prove that the rate of convergence of the multiplicative Schwarz operator for the p version grows only logarithmically in p and is independent of h.